Chinese Lexical Semantics 16th Workshop, CLSW 2015, Beijing, China, May 9-11, 2015, Revised Selected Papers - Lu, Qin.; Lu, Qin.; Gao, Hong.; Gao, Hong. (Lecture Notes in Artificial Intelligence ;, 2015)
This book constitutes the thoroughly refereed post-workshop proceedings of the 16th Chinese Lexical Semantics Workshop, CLSW 2015, held in Beijing, China, in May 2015. The 64 regular and 4 short papers included in this volume were carefully reviewed and selected from 248 submissions. They are organized in topical sections named: lexical semantics; lexical resources; lexicology; natural language processing and applications; and syntax.